PERGESERAN ADAB SANTRI KEPADA ASATIDZ DAN ASATIDZAH DI PONDOK PESANTREN AL FATTAH SIDOARJO - Isa Asrori; Ainun Nadlif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Manners are a fundamental aspect in Islamic boarding school education that reflects the respect and discipline of students towards asatidz and asatidzah. However, the dynamics of the times and external influences can affect the behavior of students in interacting with educators. The shift in the values of student manners weakens the emotional bond between students and asatidz and asatidzah. Although it does not occur evenly, this phenomenon requires special attention in maintaining the traditional values of Islamic boarding schools.